2003
DOI: 10.1021/jp021931v
|View full text |Cite
|
Sign up to set email alerts
|

Is a “Proton Wire” Concerted or Stepwise? A Model Study of Proton Transfer in Carbonic Anhydrase

Abstract: The energetics of proton transfer reactions in carbonic anhydrase (CA) have been studied with an active site model. Specifically, proton transfer from a zinc-bound water molecule to a histidine residue mediated by a numbers of water molecules was investigated. With two or three bridging water molecules, the proton transfers are fully or nearly fully concerted and only one saddle point exists. With an additional water molecule that forms a ring bridge, an intermediate is formed in which one of the water molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
182
2
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(197 citation statements)
references
References 68 publications
(117 reference statements)
12
182
2
1
Order By: Relevance
“…The general base (B) for the proton transfer is likely to be mediated by ordered waters and His64 within the enzyme, where the hydrophilic side of the active site forms the hydrogen-bonded water network (W1, W2, W2 0 , W3a and W3b) that connects W Zn to His64. This hydrogen-bonded network is believed to act as a proton wire that reduces the work required to transfer a proton from W Zn to the bulk solvent for the regeneration of the zinc-bound OH À (2) Steiner et al, 1975;Cui & Karplus, 2003;Zheng et al, 2008;Fisher, Maupin et al, 2007;Silverman et al, 1979). Neutron studies have been utilized to observe the protonation states and orientation of water molecules in proteins (Langan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The general base (B) for the proton transfer is likely to be mediated by ordered waters and His64 within the enzyme, where the hydrophilic side of the active site forms the hydrogen-bonded water network (W1, W2, W2 0 , W3a and W3b) that connects W Zn to His64. This hydrogen-bonded network is believed to act as a proton wire that reduces the work required to transfer a proton from W Zn to the bulk solvent for the regeneration of the zinc-bound OH À (2) Steiner et al, 1975;Cui & Karplus, 2003;Zheng et al, 2008;Fisher, Maupin et al, 2007;Silverman et al, 1979). Neutron studies have been utilized to observe the protonation states and orientation of water molecules in proteins (Langan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In this spirit, Eigen (20) suggested that the proton could delocalize over extended hydrogen-bonded wires. There is evidence that this behavior can occur when water molecules form isolated chains, in confined environments like proteins and nanotubes (21)(22)(23). In addition, several spectroscopic experiments examining acid-base reactions in ice and water have suggested that fast PT occurs through the formation of transient water wires (24,25).…”
mentioning
confidence: 99%
“…The structural examination of hCA II at near atomic resolution revealed that the solvent molecule W2 (the only ordered solvent molecule in the active site stabilized exclusively by other solvent molecules) is trigonally coordinated with equal distance (2.75 ± 0.02 Å) by W1, W3a, and W3b (16). Within this cluster of Significance Carbonic anhydrases catalyze the fast interconversion of carbon dioxide and water into bicarbonate and proton.…”
mentioning
confidence: 99%